COVID-19 vaccination intent among London healthcare workers. (18th May 2021) - Abuown, A; Ellis, T; Miller, J; Davidson, R; Kachwala, Q; Medeiros, M; Mejia, K; Manoraj, S; Sidhu, M; Whittington, A M; Pattani, S
Abstract: Background: The 10-month timeline from conception to regulatory approval of the Pfizer–BioNTech vaccine against SARS-CoV-2 is unprecedented in modern medicine. However, the climate of the pandemic has also seen anti-vaccination sentiments flourish. Aims: To determine the intent to accept COVID-19 vaccination among healthcare workers at a London Hospital Trust and examine variation in uptake between demographic groups. Methods: We conducted a cross-sectional survey open to staff working at the trust. Staff rated on a five-point scale the likelihood of them accepting COVID-19 vaccination. Results: We received 514 responses, representing 16% of the workforce. About 59% of staff intended to seek vaccination, 24% to reject and 17% were unsure. There was significantly reduced intended uptake in females, younger age groups, healthcare assistants, nurses, staff of black ethnic backgrounds and those who rejected influenza vaccination. Safety was the dominant concern. Conclusions: Our study finds COVID-19 vaccinate hesitancy is prevalent among healthcare workers at a London Hospital Trust. It is particularly concerning that hesitancy was highest amongst groups most exposed to COVID-19 and most at risk of severe disease. Reasons behind disparities in uptake must be addressed to protect staff and prevent deepening inequalities within the healthcare workforce.